2007
DOI: 10.1007/s00216-007-1515-5
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized monolithic disks for immunoadsorption of cardiac biomarkers from serum

Abstract: Immunoadsorbers based on 2.0 x 6.0 mm i.d., epoxy-bearing, methacrylate-based monolithic disks were developed in order to target myoglobin and N-terminal pro-natriuretic peptide (NT-proBNP), two biomarkers involved in cardiovascular disease. In both cases, antibodies were successfully coupled to the polymeric disk material. The developed immunoadsorbers permitted the selective isolation of myoglobin and NT-proBNP from human serum. Myoglobin was successfully isolated and detected from serum samples at concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The normal values of Mb in serum (3-90 ng mL −1 ) become significantly elevated after 1 h of the onset of myocardial infarction (MI) to peak in approximately 4-8 h with values from 200 to 1000 ng mL −1 [29]. Therefore, the measurement of serum Mb is applied nowadays as a biomarker of MI.…”
Section: Myoglobinmentioning
confidence: 98%
See 1 more Smart Citation
“…The normal values of Mb in serum (3-90 ng mL −1 ) become significantly elevated after 1 h of the onset of myocardial infarction (MI) to peak in approximately 4-8 h with values from 200 to 1000 ng mL −1 [29]. Therefore, the measurement of serum Mb is applied nowadays as a biomarker of MI.…”
Section: Myoglobinmentioning
confidence: 98%
“…As miniaturization is a trend in clinical diagnosis, where low concentrations and volumes are commonly used, Delmotte et al [29] developed miniaturized monolithic immunoadsorbers for MI detection. Mb from serum samples was trapped into the immnoadsorber and further analyzed by IP-RP-HPLC-ESI-MS at concentrations down to 250 fmol L −1 .…”
Section: Studies On Myoglobinmentioning
confidence: 99%
“…Human serum albumin (HSA) and inter‐α inhibitor protein were selectively captured by specific antibodies that had been immobilized on the MSP in this manner 69. In addition to the direct immobilization of antibodies via the monolith's epoxy groups, immobilization was performed via streptavidin using biotinylated antibodies (for comparison, see Section 4.2.2) 70, resulting in the enrichment of myoglobin and N ‐terminal pronatriuretic peptide from serum.…”
Section: Types Of Acmentioning
confidence: 99%
“…The streptavidin/avidin–biotin complex is highly popular for the specific immobilization of biotinylated species due to its high association constant ( K A =10 15 M −1 ) 108. Streptavidin on monolithic supports has been successfully used for the immobilization of biotinylated DNA aptamers, which then allow a specific capturing of proteins 109, 110 (Section 4.2.3) and an immobilization of antibodies (Section 4.1.1) 70. Recently, MSPs with immobilized monomeric avidin ( K A =10 7 M −1 for the monomeric avidin–biotin complex) were prepared and used to enrich biotinylated cytochrome c and biotinylated cytochrome c peptides 111.…”
Section: Types Of Acmentioning
confidence: 99%
“…They have demonstrated that the novel disks are suitable for the isolation of cardiac biomarkers from blood serum samples. Loading capacities in the high picomole range for immunoadsorbers with a bed volume as little as 22.4 μL are more than sufficient to isolate the proteins present at biologically relevant concentrations 72.…”
Section: Iacmentioning
confidence: 99%